Institucionalismo Virtual en la Educación - Palacios Osma, José Ignacio (Ingeniería, 2002)
In recent years, information technology and society have experienced a number of changes in the world. Many of these changes have set up the establishment of organizations through the net and they are known as Virtual Organizations. This paper presents a view of the future changes in Educational Systems in terms of organization and institution into Virtual Organizations. Development and implementation of a platform to the use of new technologies are not enough to be considered competitive, as functional framework which limits the regulations of these Virtual Organizations is required. This position lies on the New Institutionalism theory, as a method that allows an interdisciplinary approach to the organizations on the net.